Community Service Collaboration in Edelweiss Conservation at the Bromo Tourism Area - Muhammad Abdus Salam Jawwad; Erwan Adi Saputro; Muhammad Faisal Fadhil; Iffad Rakhmanhuda; Andyas Mukti Pradanarka; Intania Widyantari Kirana; Restu Hikmah Ayu Murti (Environmental Engineering Journal of Community Dedication, 2024)
Bromo is one of Indonesia’s premier tourist destinations, renowned for its unique biodiversity, including Edelweiss (Anaphalis javanica), a symbolic flower of mountainous ecosystems. However, increasing tourism activities and human interference have threatened the conservation of Edelweiss habitats. To address this challenge, faculty members from the Faculty of Engineering and Science, Universitas Pembangunan Nasional "Veteran" Jawa Timur, in collaboration with the local community of Bromo and international universities, conducted an Edelweiss planting program on September 26, 2024. This initiative was part of the Adjunct Professor program and the International Conference on Science and Technology (ICST) 2024. The program achieved a seedling adaptation success rate of 85%, contributing to improved soil stability in the planting areas. Beyond ecological impacts, the initiative successfully raised environmental awareness and fostered active local community participation in conservation. The collaboration among academics, the local community, and international partners highlighted the importance of multi-stakeholder approaches in environmental preservation. Despite challenges such as unpredictable weather and the need for long-term monitoring, the program serves as a model for community-based conservation initiatives in other sensitive ecosystems.